Architecting Resilience : A Framework for Secure and Compliant Healthcare IT Infrastructures - Vijaya Ashwin Jagadeesan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Healthcare information technology (IT) systems face unique challenges in maintaining data security and regulatory compliance while supporting critical patient care functions. This article provides a comprehensive analysis of the complex interplay between data protection measures and compliance requirements in the healthcare sector. We examine key components of data security, including encryption, data integrity measures, and secure transfer protocols, with a specific focus on their application to sensitive patient information. The impact of regulations such as HIPAA on system design and maintenance is explored, offering insights into the alignment of IT practices with evolving standards. Through a review of current literature and industry best practices, we present strategies for risk management, employee training, and the implementation of technical controls that address both security and compliance needs. Emerging trends, including cloud computing, the Internet of Medical Things (IoMT), and artificial intelligence in healthcare security, are discussed to provide a forward-looking perspective. This article contributes to the ongoing dialogue on balancing innovation with security in healthcare IT, offering practical recommendations for healthcare organizations to enhance their data protection measures while ensuring regulatory compliance.